Fatal Complication in Two Cases of Intubation due to Obstructive Respiratory Failure: Negative Pressure Pulmonary Edema - Ülkem Koçoğlu Barlas; Hasan Serdar Kıhtır; Mey Talip Petmezci; Nihal Akçay; Esra Şevketoğlu (Journal of Pediatric Emergency and Intensive Care Medicine, 2018)
Negative pressure pulmonary edema is a rare but potentially fatal complication that can be seen after upper and lower respiratory tract obstructions. In this paper, we aimed to present two cases of negative pressure pulmonary edema in a 18-months-old male and 3-years-old girl who were admitted to our pediatric emergency department with obstructive airway findings and did not respond to medical treatment. Both cases were admitted to the intensive care unit due to severe respiratory distress. They were intubated for low peripheral oxygen saturations and pending respiratory distress under non-invasive therapy. Significant pulmonary edema fluid observed in the tracheal tube after intubation revealed the presence of pulmonary edema additional to obstructive pathologies. The findings of pulmonary edema regressed within 48 hours by the mechanical ventilation therapy including high positive end expiratory pressure, and the cases were extubated on the third and fifth days, respectively. Patients with obstructive airway findings in pediatric emergency outpatient clinics are frequently seen and the presence of pulmonary edema may be concealed with current clinical findings and this can lead to fatal outcomes. We would like to attract attention to the importance of this kind of cases because satisfactory results can easily be seen with early diagnosis and early invasive and non-invasive treatment approaches.